Fiber Layup Generation on Curved Composite Structures. (July 2021) - Scheirer, Nathan; Holland, Stephen D.; Krishnamurthy, Adarsh
Abstract: We present a new two-step process for defining optimal composite fiber paths for use in automated fiber placement machines and finite element analysis models. Building upon work done previously in the area of discrete geodesic path generation, we present a method for predicting minimum strain energy paths initialized by fast approximate geodesic paths on triangular meshes. We compare the effectiveness of this process with those already discussed in the literature and show how this process is fast, accurate, and ready to use in commercial applications. This study also shows how this process effectively finds optimal fiber paths on complex, non-developable surfaces, which will improve finite element analysis models and provide composite manufacturers with the ability to create components with complex geometry. We have also implemented our proposed method on the GPU, which speeds up the process for large surface mesh sizes by computing geodesic paths in parallel. The algorithms developed in this study are available freely online and have been successfully integrated into an automated finite-element model-building software called De-La-Mo (https://idealab-isu.github.io/autofiber/ ). Highlights: Strain energy optimized fiber layups reduce twisting, buckling, and crossing. Geodesic parameterizations provide valuable seeding for strain energy optimization. GPU acceleration is used to reduce geodesic computation time. Optimized fiber layups can be computed even on doubly curved surfaces. Optimized fiber orientations can be easily integrated into finite element analysis.